2018
DOI: 10.1002/ange.201801058
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of a Prodrug by Thioredoxin Reductase Providing a Strategy to Target Cancer Cells

Abstract: Elevated reactive oxygen species and antioxidant defense systems have been recognized as one of the hallmarks of cancer cells. As a major regulator of the cellular redox homeostasis, the selenoprotein thioredoxin reductase (TrxR) is increasingly considered as a promising target for anticancer drug development. The current approach to inhibit TrxR predominantly relies on the modification of the selenocysteine residue in the C‐terminal active site of the enzyme, in which it is hard to avoid the off‐target effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Xinming Li et al designed a prodrug of GCB, termed S-Gem ( Figure 2 A), whose enzymatic activation can be triggered by thioredoxin reductase (TrxR) [ 7 ]. Malignant cancer cells have abnormally high levels of TrxR for maintaining their tumor phenotypes [ 8 ]; thus, it was hypothesized that prodrug activation would be selectively achieved inside the cancer cells.…”
Section: Prodrugs Of Gemcitabinementioning
confidence: 99%
“…Xinming Li et al designed a prodrug of GCB, termed S-Gem ( Figure 2 A), whose enzymatic activation can be triggered by thioredoxin reductase (TrxR) [ 7 ]. Malignant cancer cells have abnormally high levels of TrxR for maintaining their tumor phenotypes [ 8 ]; thus, it was hypothesized that prodrug activation would be selectively achieved inside the cancer cells.…”
Section: Prodrugs Of Gemcitabinementioning
confidence: 99%
“…In our efforts to develop the TRFS series fluorescent probes of TrxR, we disclosed that the 1,2-dithiolane (five-membered cyclic disulfide) scaffold could be reduced by TrxR exclusively [15,16]. Based on this discovery, we prepared a first TrxR-dependent prodrug S-Gem and demonstrated that S-Gem shows TrxR-dependent cytotoxicity [17]. Compared to the inhibition of TrxR for cancer treatment, the success of S-Gem provides a completely new strategy to develop therapeutic molecules that target TrxR.…”
Section: Prodrug Strategymentioning
confidence: 99%
“…In contrast however, 1,2-dithiolanes have also been reported as reduction-sensing units with a remarkable selectivity for TrxR. The fluorogenic TRFS-probes 16 , 18 , 45 , 46 and prodrugs 17 have been widely used for cellular studies, commercialised, and reviewed 47 51 (Fig. 1e ; overview in Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%